The Hispano-American modernist novel: phantasmagorical representations in Fabla salvaje by César Vallejo - Oré de la Cruz, Kent Wilander (2023)
This article aims to analyse and explain, based on César Vallejo’s short novel Fabla salvaje, how the phantasmagorical representations in which the characters, beings and environments of the narrative are involved are constructed and developed. Likewise, for this purpose, it is necessary to recognise and start from the central idea that this novel is inscribed within the canons of the modernist movement in its version of the decadentist narrative, where man and his individual and cultural condition are condemned to misery, to moral and spiritual destruction and to the annihilation of the traditional institutions that this movement represents, such as love and fidelity. The literary analysis will use, on the one hand, narratological and hermeneutic categories based on the recognition of the textual elements, such as the narrator, space, time and the global meaning of the text; and on the other hand, it will use the categories of literary decadentism developed by Gabriela Mora.